ANTICIPATING NEW VENTURE GESTATION OUTCOMES IN INDONESIA: INSIGHTS FROM MACHINE LEARNING TECHNIQUES - Aripin, Zaenal; Ruchiyat, Endang; Budi Raharja , Arif (KRIEZ ACADEMY : Journal of development and community service, 2024)
Machine Learning (ML) techniques have become an important instrument in analyzing data and supporting strategic decision making in various industries, including business. In the dynamic Indonesian context, ML has great potential in increasing the accuracy of predictions of market trends and consumer demand, which in turn allows companies to make better decisions in developing new businesses. This abstract explores the contribution of ML in improving understanding of market and consumer behavior, as well as the challenges faced in implementing it. ML enables in-depth analysis of market data and consumer behavior, helping companies predict future market trends, identify business opportunities, and design more effective marketing strategies. However, challenges such as availability of quality data, lack of understanding of ML, and integration with existing business processes need to be addressed. It is recommended that companies increase investment in data infrastructure and human resource training in ML, as well as strengthen collaboration between the private sector, government and academic institutions. By overcoming these challenges, companies can harness the full potential of ML to increase their competitive advantage, create significant added value, and optimize business growth opportunities in Indonesia.